2015
DOI: 10.1017/s0029665115002451
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrate and control of hepatic gene expression: mechanistic links from ATP and phosphate ester homeostasis to the carbohydrate-response element-binding protein

Abstract: Type 2 diabetes and non-alcoholic fatty liver disease (NAFLD) are associated with elevated hepatic glucose production and fatty acid synthesis (de novolipogenesis (DNL)). High carbohydrate diets also increase hepatic glucose production and lipogenesis. The carbohydrate-response element-binding protein (ChREBP, encoded byMLXIPL) is a transcription factor with a major role in the hepatic response to excess dietary carbohydrate. Because its target genes include pyruvate kinase (PKLR) and enzymes of lipogenesis, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 93 publications
(220 reference statements)
1
37
1
Order By: Relevance
“…In the current study, almost no labeling of UDP‐glucose from 13 C‐glucose could be observed in L‐ G6pc −/− mice, reflected in a 95% decrease of the GCK flux, which may represent a response to maintain phosphate homeostasis in the liver . Thus, the hepatic phosphorylation of infused 13 C‐glucose and its subsequent intrahepatic metabolism are strongly reduced in L‐ G6pc −/− mice.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In the current study, almost no labeling of UDP‐glucose from 13 C‐glucose could be observed in L‐ G6pc −/− mice, reflected in a 95% decrease of the GCK flux, which may represent a response to maintain phosphate homeostasis in the liver . Thus, the hepatic phosphorylation of infused 13 C‐glucose and its subsequent intrahepatic metabolism are strongly reduced in L‐ G6pc −/− mice.…”
Section: Discussioncontrasting
confidence: 55%
“…(38) In the current study, almost no labeling of UDPglucose from 13 C-glucose could be observed in L-G6pc 2/2 mice, reflected in a 95% decrease of the GCK flux, which may represent a response to maintain phosphate homeostasis in the liver. (41) Thus, the hepatic phosphorylation of infused 13 C-glucose and its subsequent intrahepatic metabolism are strongly reduced in L-G6pc 2/2 mice. Intrahepatic 13 C-glucose metabolism leads to "scrambling" of the label after the reentering of 13 C-labeled glycolytic intermediates into gluconeogenesis, a phenomenon referred to as "glucose carbon recycling."…”
Section: Discussionmentioning
confidence: 96%
“…1E). The elevation in G6P by S4048 in hepatocytes and in vivo (24 -26) supports the role of glucose 6-phosphatase in maintaining G6P homeostasis (16,17). Metformin did not lower G6P in hepatocytes incubated with 5 mM glucose (Fig.…”
Section: Metformin Lowers Cell G6p When Raised With High Glucose or Gsupporting
confidence: 57%
“…This effect of glucose is often described as glucotoxicity because induction in G6pc and, thereby, hepatic glucose production by hyperglycaemia is counter‐intuitive. However, repression of Gck and induction of G6pc by high glucose can be rationalized as a mechanism for preserving intracellular metabolite homeostasis at the expense of worsening hyperglycaemia . In this study we tested the hypothesis that treatment of hepatocytes with a GKA represses the Gck gene by a mechanism linked to raised cell metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…However, repression of Gck and induction of G6pc by high glucose can be rationalized as a mechanism for preserving intracellular metabolite homeostasis at the expense of worsening hyperglycaemia. 16 In this study we tested the hypothesis that treatment of hepatocytes with a GKA represses the Gck gene by a mechanism linked to raised cell metabolites. We also tested whether metformin, which has effects on glucokinase translocation opposite to those of GKAs, [17][18][19] also has effects on cell metabolites and gene regulation at high glucose that are converse to those of the GKA.…”
mentioning
confidence: 99%